FENOMENA IMPOSTOR SYNDROME PADA MAHASISWA BERPRESTASI (MAWAPRES) UNIVERSITAS ISLAM “45” BEKASI - Alfiana Indah Muslimah; Septia Catur Amalia; Alfiyah Nur Jauharah; Yunita Kurniawati; Alifah Qisthi Fadhiilah (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2022)
Outstanding students are students who have succeeded in achieving high achievements, both curricular, co-curricular, and extra-curricular according to the specified criteria. However, the learning outcomes that lead to these achievements sometimes make some students feel that they do not deserve the award. In psychology, it is often referred to as the impostor phenomenon or known as the impostor syndrome. This qualitative study aims to determine whether or not there is an impostor syndrome phenomenon in outstanding students (MAWAPRES) at the Islamic University "45" Bekasi. The participants of this study were 2 people, namely the main informant and the supporter. Based on the results of data analysis, this can be seen from several aspects of the existing impostor syndrome such as the luck factor, help from other people and doubting the value they get at the end of each semester. The results of this study explain that impostor syndrome can occur to everyone.